Asiatic Society, located at Town Hall - Ghosh, Ayan (2023)
Horniman Circle was built in front of the Town Hall, on a large open space known as Bombay Green. In the 1830s, it became the premises of the Asiatic Society, Mumbai. The Society was formed in 1804, by Scotsman Sir James Mackintosh, aimed at “promoting useful knowledge, particularly such as its now immediately connected with India.”